HISTORICAL RECORDS OF FATTY ACIDS IN AN ICE CORE FROM SITE-J, GREENLAND - カワムラ, キミタカ; スズキ, イクコ; フジイ, ヨシユキ; ワタナベ, オキツグ; KAWAMURA, Kimitaka; SUZUKI, Ikuko; FUJII, Yoshiyuki; WATANABE, Okitsugu (National Institute of Polar Research, 1995)
P(論文) Homologs of normal and branched chain saturated fatty acids, as well as unsaturated fatty acids, were determined in an ice core (205m long) taken from Site-J, Greenland using capillary gas chromatography and mass spectrometry. Molecular distributions of normal saturated fatty acids (C_8-C_<32>) were characterized by an even carbon number predominance with two maxima at C_<16> and C_<24> or C_<22>, suggesting that they are transported long range through the atmosphere over Greenland from both marine and continental biological sources. Unsaturated fatty acids (C_<14>-C_<22>) were abundantly detected in the ice samples with oleic acid (C_<18 : 1>) being predominant. This is in contrast to the remote marine aerosols in which unsaturated fatty acids are depleted due to photochemical oxidation, suggesting that the fatty acids settled down in the Greenland ice sheet without serious photochemical degradation during atmospheric transport. Concentrations of the fatty acids (C_<12>-C_<32>) in the ice core fluctuated in the range of 3.9-104μg/kg-ice with higher values at around 1800,1900-1950,and 1980 AD. Relative abundances of the higher molecular weight fatty acids (C_<20>-C_<32>) were higher (10-30% of total fatty acids) in 1700-1850 AD, and lower (5-8%) in 1920-1950 AD. These results suggest that atmospheric transport of continentally derived materials over Greenland was relatively enhanced in 1700-1850 AD, whereas the transport of marine derived organic matter was significantly intensified in 1920-1950 AD. departmental bulletin paper